Training workshops: Strengthening and competitiveness in initial training IESPPA - Silvia Quispe Flores (2019)
Teacher training must now respond to the needs of the context, that is, it must be prepared to face the generation of young people who have technology as a resource that is used from different perspectives and should introduce new alternatives that allow also direct that generation to develop potentials that can not be forgotten, if not on the contrary to teach them to coexist with those elements, the training workshops aim to develop those professional skills that technology can not address which is the contact of human warmth, development of emotional intelligence to rethink the system of life in contact with nature that needs a lot of us to gain ground in the relationship with man.